Comparative evaluation of conventional and modified Hughes procedures in reconstructing large full-thickness defects of the lower eyelid - Lei Zhang; Ye Pan; Jiagen Li; Hong Zhao (JPRAS Open)
Purpose: To introduce a modified Hughes procedure for the repair of large full-thickness defects of the lower eyelid. Methods: This retrospective study included 56 patients: 30 in the conventional group treated with a Hughes flap and 26 in the modified group treated with a full-thickness upper eyelid flap pedicled with levator aponeurosis, Muller muscle and conjunctiva. The reconstruction time, period of pedicle division and complication rates were evaluated. Results: The lower eyelid reconstruction time was 89.2±7.7 minutes in the conventional group and 61.7±7.5 minutes in the modified group, whereas the period of pedicle division was 21.1±3.0 days in the conventional group and 10.8±3.0 days in the modified group, and the differences were statistically significant (p = 0.000 and 0.000). Lower eyelid retraction was 0.4±0.4 mm in the conventional group and 0.1±0.2 mm in the modified group, and the difference was statistically significant (p = 0.001). Conclusion: The modified Hughes procedure in this study resulted in a shorter lower eyelid reconstruction time, a shorter period of pedicle division, and a lower degree of lower eyelid retraction. This technique is simple and convenient for reconstructing large full-thickness defects of the lower eyelid.